2009
DOI: 10.1097/imi.0b013e3181a20da6
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Coronary Artery Bypass Grafting is Associated with Reduced Operative Mortality and In-Hospital Adverse Events in Patients with Left Main Coronary Artery Disease

Abstract: Objective Left main coronary artery disease (LMD) is a known risk factor for perioperative complications. This study compares off-pump coronary artery bypass (OPCAB) versus on-pump coronary artery bypass (ONCAB) grafting, CABG, with respect to in-hospital death, stroke, myocardial infarction, and major adverse cardiac events (MACE) in CABG patients with and without LMD. Methods Among 13,108 consecutive iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…With regard to short-term stroke risk, a metaanalysis of 59 randomized trials (n = 8,961) associated OPCAB with a 30 % reduction in 30-day stroke risk [ 107 ]. This is consistent with the results of two large, propensitymatched registry studies (CREDO-Kyoto [ 111 ] [n = 6,323] and a 2008 study by Puskas et al [ 104 ] [n = 12,812]) and a large retrospective study (n = 13,108) [ 105 ], all of which showed lower short-term stroke rates in OPCAB patients than in CABG patients. In contrast, the ROOBY trial [ 109 ], the CORONARY trial [ 98 ], and a very large (n = 63,047) Veterans Administration registry study [ 108 ] found no differences in short-term stroke rates.…”
Section: Results Of Off-pump Coronary Artery Bypasssupporting
confidence: 83%
“…With regard to short-term stroke risk, a metaanalysis of 59 randomized trials (n = 8,961) associated OPCAB with a 30 % reduction in 30-day stroke risk [ 107 ]. This is consistent with the results of two large, propensitymatched registry studies (CREDO-Kyoto [ 111 ] [n = 6,323] and a 2008 study by Puskas et al [ 104 ] [n = 12,812]) and a large retrospective study (n = 13,108) [ 105 ], all of which showed lower short-term stroke rates in OPCAB patients than in CABG patients. In contrast, the ROOBY trial [ 109 ], the CORONARY trial [ 98 ], and a very large (n = 63,047) Veterans Administration registry study [ 108 ] found no differences in short-term stroke rates.…”
Section: Results Of Off-pump Coronary Artery Bypasssupporting
confidence: 83%